Would Screening for Lung Cancer Benefit 75- to 84-Year-Old Residents of the United States? - Varlotto, John; DeCamp, Malcolm M.; Flickinger, John; Lake, Jessica; Recht, Abram; Belani, Chandra; Reed, Michael; Toth, Jennifer; Mackley, Heath; Sciamanna, Christopher; Lipton, Alan; Ali, Suhail; et al. (Frontiers in Oncology, 2014)
Background: The National Lung Screening Trial demonstrated that screening for lung cancer improved overall survival (OS) and reduced lung cancer mortality in the 55-74-year-old age group by increasing the proportion of cancers detected at an early stage. Because of the increasing life expectancy of the American population, we investigated whether screening for lung cancer might benefit men and women aged 75-84 years. Materials/Methods: Rates of non-small cell lung cancer (NSCLC) from 2000-2009 were calculated in both these younger and older age groups using the Surveillance Epidemiology and End Reporting (SEER) database. OS and lung cancer -specific survival (LCSS) in patients with Stage I NSCLC diagnosed from 2004-2009 were analyzed to determine the effects of age and treatment. Results: The per capita incidence of NSCLC decreased in the 55-74 cohort, but increased in the 75-84 cohort over the study period. Crude lung cancer death rates in the two age groups who had no specific treatment were 39.5% and 44.9%, respectively. These rates fell in both age groups when increasingly aggressive treatment was used. Rates of OS and LCSS improved significantly with increasingly aggressive treatment in the 75-84 age group. The survival benefits of increasingly aggressive treatment in 75-84 year old females did not differ from their counterparts in the younger cohort. Conclusions: Screening for lung cancer might be of benefit to individuals at increased risk of lung cancer in the age 75-84 group. The survival benefits of aggressive therapy are similar in females between 55-74 and 75-84 years old.